Plastic Bronchitis: A Case Report - Andressa Oliveira Peixoto; José Dirceu Ribeiro; Rafael Miranda da Costa; Fernando Augusto Lima Marson (Global Journal of Allergy - Peertechz Publications, 2017)
Plastic bronchitis is a rare disease characterized by the formation of bronchial casts that can cause partial or complete obstruction of the airway. In this case report, a patient aged four years, previously healthy, began a chronic cough and underwent repeated courses of antibiotic therapy, inhaled corticosteroids and imaging tests; until there was a spontaneous sputum of a bronchial tree-shaped cast with approximately five cm, making possible the diagnosis of plastic bronchitis, which in our case report has idiopathic etiology. Due to the rarity of the pathology, we believe in the importance of the case report that can help to: (i) better understand the clinical presentation of plastic bronchitis; (ii) understand the difficulty in diagnosing the disease and distinguishing associated pathologies; (iii) disseminate the disease to health professionals; (iv) better understand the available therapies; (v) evaluate the efficacy of the disease treatment.